ORGANIZATIONAL BEHAVIOR AND BUSINESS PSYCHOLOGY - Melibаevа , Gulxоn (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
This article provide delves into the interconnected fields of organizational behavior and business psychology, which explore the intricate dynamics shaping individual and group behavior in the workplace. Business psychology, a subfield of psychology, focuses on applying psychological theories to enhance workplace well-being and productivity. Meanwhile, organizational behavior studies how organizational structures influence employee performance and overall success. Both fields face challenges, including ethical considerations, cultural diversity, and the complexity of leadership. To address these challenges, researchers advocate for interdisciplinary collaboration, methodological advances, and ethical research practices. By navigating these complexities, scholars contribute not only to academic knowledge but also to practical solutions for optimizing organizational performance. In an ever-evolving business environment, understanding human behavior remains paramount for sustained success.